Bat Influenza A(HL18NL11) Virus in Fruit Bats, Brazil - Almeida Campos, Angelica Cristine; Bentim Goes, Luiz Gustavo; Moreira-Soto, Andres; Carvalho, Cristiano de [UNESP]; Ambar, Guilherme [UNESP]; Sander, Anna-Lena; Fischer, Carlo; Rosa, Adriana Ruckert da; Oliveira, Debora Cardoso de; Kataoka, Ana Paula G.; Pedro, Wagner Andre [UNESP]; Martorelli, Luzia Fatima A.; et al. (Centers Disease Control & Prevention, 2019)
Screening of 533 bats for influenza A viruses showed subtype HL18NL11 in intestines of 2 great fruit-eating bats (Artibeus lituratus). High concentrations suggested fecal shedding. Genomic characterizations revealed conservation of viral genes across different host species, countries, and sampling years, suggesting a conserved cellular receptor and wide-ranging occurrence of bat influenza A viruses.